ANALYSIS OF STRESSES IN AN INFINITE ELASTIC BODY WITH A LOCALLY CURVED COVERED NANOFIBER - Alan, K. S.; Akbarov, S. D. (SPRINGER, 2011)
Within the framework of a piecewise homogeneous body model, with the use of the three-dimensional geometrically nonlinear exact equations of the theory of elasticity, the method developed for determining the stress distribution in nanocomposites with unidirectional locally curved covered nanofibers is used to investigate the normal stresses acting along nanofibers. The investigation is carried out for an infinite elastic body containing a single locally curved covered nanofiber in the case where there exists a bond covering cylinder of constant thickness between the nanofiber and the matrix material. It is assumed that the body is loaded at infinity by uniformly distributed normal forces in the fiber direction. Upon formulation and mathematical solution of the boundary value problem, the boundary form perturbation method is used. Numerical results for the stress distribution in the body and the influence of geometrical nonlinearity on this distribution are presented and interpreted.
Keywords: nanocomposites; nanofiber; covering material; local curvature; geometrical nonlinearity; stress distribution; 3-DIMENSIONAL THEORY; CARBON NANOTUBE; MECHANICS; STABILITY; Materials Science; Polymer Science